CRISPR/Cas9 Application for Gene Copy Fate Survey of Polyploid Vertebrates - Yin, Fanqian; Liu, Wenfu; Chai, Jing; Lu, Bin; Murphy, Robert W.; Luo, Jing (Frontiers in Genetics, 2018)
Polyploidization occurs widely in eukaryotes, and especially in plants. Polyploid plants and some fishes have been commercialized. Typically, severe genomic perturbations immediately follows polyploidization and little is known about how polyploid offspring survive the genetic and epigenetic changes. Investigations into this require the identification of genes related to polyploidization and the discrimination of dosage-balance from paternal and maternal copies, and regardless of the mechanism being either autopolyploidization or allopolyploidization. New approaches and technologies may discern the mosaic of novel gene functions gained through the recombination of paternal and maternal genes in allopolyploidization. Modifications of Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) with CRISPR-associated system (Cas) protein 9 (CRISPR/Cas9) have been employed in studies of polyploidization of plants. However, the approach has seldom been applied to polyploidization in vertebrates. Herein, we use CRISPR/Cas9 to trace gene-fate in tetraploid goldfish, and specifically to identify the functional differentiation of two divergent copies of fgf20a, which are expressed differently throughout embryonic development. We expect this gene editing system will be applicable to studies of polyploids and the genetic improvement of polyploid livestock.